PENGARUH IKLIM ORGANISASI TERHADAP STRES KERJA PADA KARYAWAN PT.PAL SURABAYA - Reynaldi Novian Lantang; Gartinia Nurcholis; Dessy Nur Utami (Jurnal Psikologi Poseidon, 2022)
The purpose of this study was to determine the effect of organizational climate on work stress on employees of PT. PAL Indonesia (Persero) Indonesia General Engineering Division, this study used a quantitative approach with survey methods and used simple linear regression analysis techniques. Data collection used a work stress scale of as much as 38 Items, and the Organizational Climate Scale of 42 Items. The number of subjects in this study were 75 employees of PT. PAL Indonesia (Persero) Surabaya General Engineering Division. The sampling technique in this study used Accidential Sampling. Finding in this study showed that Organizational Climate affects Work Stress at PT. PAL Indonesia (Persero) Surabaya General Engineering Division. The results showed that the level of work stress owned by employees of PT. PAL Indonesia (Persero) Surabaya General Engineering Division was in the low category.